2002
DOI: 10.1038/sj.cgt.7700505
|View full text |Cite
|
Sign up to set email alerts
|

Growth suppression by a p14ARF exon 1β adenovirus in human tumor cell lines of varying p53 and Rb status

Abstract: We have analyzed the ability of an adenoviral vector encoding the exon 1b region of the p14 ARF tumor suppressor ( ARF ) to suppress the growth and viability of an array of tumor cell lines of various origins and varying p53 and Rb status, in order to establish the clinical potential of ARF. An important activity of ARF is regulation of p53 stability and function through binding to the mdm2 protein. By sequestering mdm2, ARF may promote growth suppression through the Rb pathway as well because mdm2 can bind to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 41 publications
1
33
0
4
Order By: Relevance
“…These data indicate that Siva1 regulates p53 expression in an Mdm2-dependent manner. As ARF and p53 are frequently mutated in cancer cells, generally in a mutually exclusive manner 20 , we next used a primary human fetal lung fibroblast cell line to further confirm the effect of Siva1 on the ARF-p53 pathway. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that Siva1 regulates p53 expression in an Mdm2-dependent manner. As ARF and p53 are frequently mutated in cancer cells, generally in a mutually exclusive manner 20 , we next used a primary human fetal lung fibroblast cell line to further confirm the effect of Siva1 on the ARF-p53 pathway. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The direct binding of Siva1 to ARF appears to be required for the rapid degradation of ARF, as supported by the finding that the mutant Siva1DC, which is unable to interact with ARF, has no effect on the stability and ubiquitination of ARF. Additionally, we show that the N-terminal domain (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] of ARF is involved in its interaction with Siva1, but is not essential for this association. As this N terminus (amino acids 2-14) has been well recognized as a critical region for binding to Mdm2, it is not surprising to see that Siva1 could compete with Mdm2 to bind to ARF.…”
Section: Articlementioning
confidence: 99%
“…41 In the past 2 years, more interest has focused on p14 Arf . Several reports have demonstrated that adenoviral delivery of the p14 Arf gene is capable of inducing cell cycle arrest and apoptosis in a wide variety of tumour models [42][43][44][45][46][47] and can sensitize cells to chemotherapy. 48 Initial reports suggested that intact p53 pathways were required for p14 Arf -mediated cytotoxicity [47][48][49] and that cotransfection with wild-type p53 could enhance the p14 Arf effect.…”
Section: Ink4/arf Locus Provides Two Potential Targets For Gene Therapymentioning
confidence: 99%
“…Both cell lines express endogenous ARF (22). The MCF-7 subclone expresses endogenous wild-type p53 and lacks endogenous ARF (22). Cell lines were maintained as described previously (23).…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability assays were carried out in 96-well plates as described previously (22,23). Briefly, cells grown in medium lacking phenol red were either treated with UV-C radiation using a Stratalinker (Stratagene, La Jolla, CA) and replated in 96-well plates at 10,000 cells per well or treated with adenoviral vectors for 3 hours (22) followed 1 day later by treatment with UV-C radiation and replating.…”
Section: Introductionmentioning
confidence: 99%